Profit Efficiency of Bangladeshi Banks: A Stochastic Frontier Approach - Jilhajj, Khondokar (International Journal of Economics and Financial Issues, 2023)
This paper examines the profit efficiency of the banks in Bangladesh using the stochastic frontier analysis. The paper is prepared based on the secondary data only and the sample contains data from 25 banks including state owned and private conventional banks in Bangladesh from the year 2011 to 2020. Translog function has been employed to construct the profit function and Battese and Coelli 1995 (BC95) model has been used to determine the profit efficiency. The efficiency performance reveals that, on average, banks in Bangladesh are 80.73% profit efficient. Dutch-Bangla Bank Limited (DBBL) is the most profit efficient banks with a score of 92.56% in 2020. While Dhaka Bank is the least profit efficient banks with a score of 15.42%. Banks belong to the 3rd and 2nd generation are the most profit efficient. Besides, none of the inefficiency determinant is statistically significant to explain variation in the profit inefficiency as the dataset is small and only limited to Bangladeshi banks. Moreover, diagnostic tests such as Normality test, M3T statistics test and Likelihood Ratio (LR) test have been performed to confirm the existence of inefficiency. This report shall provide important insight of state owned and private conventional banks in Bangladesh to the managements, regulators and other concerned parties.